Factor Affecting Perineal Wound Healing - Esti Handayani; Herlina Tri Damailia; Wahyu Pujiastuti (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2020)
Perineal wound cause many problems, likea as many as 70% of postpartum mothers have difficulty defecating, 60% of postpartum mothers have difficulty with mictie, 30% of postpartum mothers complain of UTI signs, 60% of breast milk is substandard so that formula milk is added and 10% of mothers with subinvolution uteri. Perineal wound can heal immediately if the postpartum mother has a good hemoglobin level, to get enough hemoglobin, one of them is by consuming Fe tablets and vitamin C. It was found that as many as 60% of postpartum women with perineal wound healing 8 to 14 days. The goals of this research is to find factors that affecting perineal wound healing.This type of research is correlational analytic with cross sectional time approach. The population is postpartum mothers in the working area of Kedu Public Health Center, Temanggung Regency, from September to November 2018. The samples were obtained using quota sampling sampling with 40 postpartum mothers. Spearman rank test showed results of haemoglobin level and perineal wound care related to the speed of healing of perineal wounds (pvalue of hb level 0.00 and pvalue perineal wound care 0.027), multivariat test using linear regression where there is influence of hemoglobin level and perineal care to the speed of perineal wound healing (pvalue 0,021).Midwives are expected to screen haemoglobin levels and monitor perineal wound care performed by the mother to prevent delays in healing perineal wounds Keywords: BMI, age, hemoglobin level, perineal care,perineal wound healing